Sosialisasi Kebijakan Pengadaan Tanah Bagi Pembangunan Dalam Perspektif Reformasi Agraria - Absori Absori; Kelik Wardiono; Wardah Yuspin; Arief Budiono; Fahmi Fairuzzaman; Moh. Indra Bangsawan (Politeknik Negeri Cilacap, 2022)
The right to control from the state is a right that at the highest level is controlled by the state as an organization of power for all the people. This right gives the state authority as stated in Article 2 paragraph (2) of the UUPA. However, these various regulations and policies at the level of implementation do not harm the principles of the rights of the Indonesian people. The presence of the Job Creation Law which regulates land acquisition for development is considered pragmatic, more oriented towards investment and economic interests so it is considered to ignore the ideals and rights as well as the spirit of agrarian reform that favours the interests of farmers. The right of control of this state builds relations between the state and the nation, namely a kind of customary rights relationship that is raised at the highest level, namely the level that affects the entire territory of the country. The meaning of being controlled by the state contained in Article 33 of the 1945 Constitution is not explicitly formulated in its explanation. This allows the emergence of various interpretations of the meaning of this service trying to socialize land acquisition policies in the context of agrarian reform.